The frequently evaluation of topic no.1 of the methodology an theory of physical education by the virtual classroom - Marlen de la Caridad Labrador Vento; Zoraida Hernández Barredo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2012)
The evaluation presents an educational regulator function system. Not only controls is the product, also infers in the mode knowledge relationship of the students, the students between them, the teachers with parents. Among the fundamental forms of evaluation are frequently those that are produced in a teaching process in fact and they are daily and systematically. The methodology and Theory of Physical Education as an object is understood, as on area of knowledge, that identifies like a specific pedagogy of physical education. For the study it has 3 themes: No. 1 Fundamental Theories Conceptions of Physical Education, that in fact presents the most volume of theory content and at the same time is very problematic for systematically evaluation, because of many students are not in the moment of evaluation and it looses the great importance and the teaching process in fact is aim to solve an specific problem, that is, the participation is less than 30% and the 98% tell the topic is not very important as their point of view. For all we have exposed, decided make a frequently evaluation of topic No. 1 of the object Methodology an Theory of Physical Education by the virtual classroom, obtaining more attention and disposition of the students, achieving in them more than 85% in frequently evaluation through them we got their a cognitive self knowledge process, the demanding situation characteristics and the task to solve being undoubtedly as an essential component of learning and at the same time raising the evaluation process.